2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1615324
|View full text |Cite
|
Sign up to set email alerts
|

Building a High-Quality Mobile Telemedicine System using Network Striping over Dissimilar Wireless Wide Area Networks

Abstract: Abstract-This paper describes an approach to building a high-quality mobile telemedicine system that overcomes the limitations of individual public wireless data networks. Public wireless data channels do not have the capacity to handle the high-bandwidth video needed for applications such as remote evaluation of trauma and stroke patients. Network striping allows us to aggregate multiple physical channels to meet the bandwidth requirements for the video. We have developed flexible network-striping software mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…With the explosive growth of the number of medical images and the popularity of location-based service (LBS), locationbased medical image retrieval and browsing has been paid much attention to recently in mobile telemedicine systems (MTS) [1]. Telemedicine is the use of telecommunication and information technologies to provide clinical health care at a distance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the explosive growth of the number of medical images and the popularity of location-based service (LBS), locationbased medical image retrieval and browsing has been paid much attention to recently in mobile telemedicine systems (MTS) [1]. Telemedicine is the use of telecommunication and information technologies to provide clinical health care at a distance.…”
Section: Introductionmentioning
confidence: 99%
“…There is no existing study on the multiple image transmission performance improvement from the perspective of the image batching, especially in the MTS environment. So to further speed up the transmission processing and improve user experiences, the paper proposes a Multiple Transmission Optimization method for large medical images 1 in the MTS environment, called the MTO, by exploring the content correlation of the transmission images. 1 By default, the medical images in this paper refer to the grayscale image.…”
Section: Introductionmentioning
confidence: 99%
“…in terms of reduced number of trips to the emergency room (Kumekawa, 2000), wireless monitoring promises further improvements by providing continuous monitoring, patient mobility, and improving patient compliance with frequent and better quality measurements (Kumekawa, 2000). When appropriate health professionals cannot be physically present to diagnose patients, telecommunications technology can be used to connect these professionals to those in need of their expertise (Qureshi et al, 2005). In hospitals and homes, telemedicine has been shown to reduce the cost of health-care and increase efficiency through better management of chronic diseases, shared E-mail address: palanivelrajanme@gmail.com age of 25.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with heart arrhythmia usually need to be monitored and controlled in hospital for one to several days. These patients are treated to reach on normalizing their heart arrhythmia or achieve an average heart frequency (Qureshi et al, 2005). Sometimes it is necessary to monitor some heart patients in longer periods of time to provide more certain documentation for the treatment's correctness, but the patients often are released from the hospital to give the priority to other heart patients on the waiting list, whom need to be hospitalized immediately.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, hand-held devices especially PDAs and smart phones have been reported to become increasingly prevalent for health care delivery (Trevor et al, 2004;Wickramasinghe et al, 2004;Baldwin, 2005). Research efforts and the use of wireless communications technologies to extend the reach, range and maneuverability of health care applications are covered in (Kyriacou et al, 2003;Voskarides et al, 2002;Mobile, n. d;James, 1996;MobilePoint, 2004); Kugean, 2002;Qureshi, 2005;Robert, 2005;Aura, 2006;Kim, 2005;Tang, 2004). Other research work that demonstrate the feasibility, convenience, and efficiency of using handheld devices in enhancing care delivering in areas such as transferring clinical data (Kim, 2005;Tang, 2004), electronic messaging systems (Wojceichowski et al, 2006;Wojciech et al, 2008;ng, 2007) have also been widely reported.…”
Section: Introductionmentioning
confidence: 99%